Thermal Stress Analysis of Jet Impingement Cooling of a Solid Block. Issue 1 (15th December 2023) - Saeid, Nawaf H.
Abstract: The conjugate heat transfer and the generated thermal stresses of jet impingement cooling of a solid block are considered for numerical investigation. A rectangular block is heated from the bottom surface and is cooled by impinging air on its top surface. The selected materials of the block are: Polyethylene, Titanium alloy, Aluminum alloy, and Carbon steel. The governing parameters in the present study are Reynolds number, temperature of the bottom surface of the block, material, and thickness of the block. It is found that the average Biot number for the Aluminum alloy block is the minimum. The average values of Bi are increased with the increase of the Reynolds number of the jet, the thickness of the block or the heated surface temperature. The maximum equivalent stress is generated at the maximum temperature gradient under the stagnation point of the jet flow. The generated equivalent stress increased by increasing either the heated surface temperature or the thickness of the block. The maximum total deformation is found in the Polyethylene block and the minimum occurred for the Titanium Alloy block. The results show negligible effects of Reynolds number on the equivalent stresses and total deformation of the block.